The caddisflies from Serra dos Órgãos National Park, Rio de Janeiro, Brazil, with the description of two new species of Ochrotrichia Mosely (Trichoptera: Hydroptilidae: Ochrotrichiinae) - Santos, Allan Paulo Moreira; Marques, Raquel Almeida; Henriques-Oliveira, Ana Lucia; Alves, André Almeida; Dumas, Leandro Lourenço (Zootaxa, 2022)
The Serra dos Órgãos National Park (PARNASO) is a federal conservation unit located in Rio de Janeiro State, within the Atlantic Forest biome. This biome is one of the world’s biodiversity hotspots and has high diversity and endemism of caddisfly taxa. Here, we present a checklist of caddisflies from PARNASO, including the description of two new species of Ochrotrichia Mosely (Hydroptilidae). Ochrotrichia sino sp. nov. and Ochrotrichia papel sp. nov. are assigned to the O. aldama Species Group due to the divided tergum X in male genitalia, although in the first one tergum X is not simple as in most species in this group. Ochrotrichia sino sp. nov. is recognized by tergum X having a broad basal portion bearing a basodorsal spine-like process on the left side and the apical portion with two elongate processes, one curved and crossing the other one underneath. Ochrotrichia papel sp. nov. is distinguished by the elongate inferior appendages, by tergum IX having its posterior margin obliquely emarginate, and tergum X being divided into two processes, the left one longer and almost straight, the right one curved to the left, slightly upturned in lateral view. The list of PARNASO species is based on isolated records in literature and on specimens in the Coleção Entomológica Professor José Alfredo Pinheiro Dutra, Universidade Federal do Rio de Janeiro (Departamento de Zoologia) [UFRJ (DZRJ)], with samples collected since 2009. A total of 95 species were recorded from the PARNASO, of which eight are new distributional records for Rio de Janeiro State. Hydroptilidae (27 spp.), followed by Hydropsychidae (13 spp.), Leptoceridae, and Philopotamidae (12 spp. each) are the families with highest species richness. Before this work, only about 20 species of caddisflies were formally registered from the park area. In this way, this work is an important contribution to fill the gaps of knowledge caused by “Wallacean” and “Linnean” shortfalls.